2012
DOI: 10.4073/csr.2012.3
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Based Stress Reduction (MBSR) for Improving Health, Quality of Life, and Social Functioning in Adults

Abstract: Mind‐body interventions to manage stress‐related health problems are of widespread interest. One of the best known methods is mindfulness‐based stress reduction (MBSR), and MBSR courses are now offered by health services, as well as in social and welfare settings. In this systematic review, we report on the effects of MBSR interventions on health, quality of life, and social functioning. From the more than 3,000 potentially relevant references identified in two extensive searches, we included 31 relevant studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
133
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(145 citation statements)
references
References 175 publications
7
133
0
5
Order By: Relevance
“…Consistent with the emerging empirical evidence [30][31][32][33][34][35][36][37][38][39][40] as well as the general consensus of clinicians, researchers, and the general public, it is concluded that MBIs have the potential to play an important role in psychiatric treatment settings as well as in applied psychological settings more generally. However, due to the rapidity at which mindfulness has been taken out of its traditional Buddhist setting, and what is possibly evidence of media and/or scientific hype concerning the potency of mindfulness [5], it is recommended that future research seeks to (i) consolidate and replicate research findings, (ii) assess the maintenance of outcomes over longer time periods, (iii) investigate potential adverse effects, (iv) fully control for potential performance bias in MBI intervention studies, (v) formulate comprehensive training and supervision curricula -that are informed by the traditional meditation literature -for secular MBI instructors, and (vi) investigate the Buddhist position that sustainable improvements to mental (and spiritual) health typically require consistent daily mindfulness practice over a period of many years (i.e., they do not arise after attending eight two-hour classes with some self-practice in between).…”
Section: Does the Evidence Match The Momentum?mentioning
confidence: 59%
See 1 more Smart Citation
“…Consistent with the emerging empirical evidence [30][31][32][33][34][35][36][37][38][39][40] as well as the general consensus of clinicians, researchers, and the general public, it is concluded that MBIs have the potential to play an important role in psychiatric treatment settings as well as in applied psychological settings more generally. However, due to the rapidity at which mindfulness has been taken out of its traditional Buddhist setting, and what is possibly evidence of media and/or scientific hype concerning the potency of mindfulness [5], it is recommended that future research seeks to (i) consolidate and replicate research findings, (ii) assess the maintenance of outcomes over longer time periods, (iii) investigate potential adverse effects, (iv) fully control for potential performance bias in MBI intervention studies, (v) formulate comprehensive training and supervision curricula -that are informed by the traditional meditation literature -for secular MBI instructors, and (vi) investigate the Buddhist position that sustainable improvements to mental (and spiritual) health typically require consistent daily mindfulness practice over a period of many years (i.e., they do not arise after attending eight two-hour classes with some self-practice in between).…”
Section: Does the Evidence Match The Momentum?mentioning
confidence: 59%
“…As a consequence of these findings, both the American Psychiatric Association (US) and the National Institute for Health and Care Excellence (UK) advocate the use of MBCT in the treatment of recurrent depression in adults [3]. There is also preliminary evidence that supports the use of MBIs in the treatment of a broad range of mental health issues including (but not limited to) schizophrenia-spectrum disorders, addiction disorders (both chemical and behavioral), bipolar disorder, post-traumatic stress disorder, eating disorders, and anger dysregulation [33][34][35].…”
Section: Does the Evidence Match The Momentum?mentioning
confidence: 99%
“…These findings are consistent with findings of Fleer et al [35] who reported effectiveness of MBCT for the treatment of seasonal affective disorder and Williams et al [36] reported effectiveness of MBCT for preventing relapse in recurrent depression. And Sedaghati, Younesi and Sedaghati conducted a research on the effectiveness of MBCT on the quality of life in mothers of children with cerebral palsy and their findings revealed that MBCT program improved the quality of life of the participants [37].…”
Section: Discussionmentioning
confidence: 99%
“…Mindfulness-based interventions have shown promising therapeutic outcomes for several psychological and physical disorders, such as chronic pain, depression, postpartum depression, anxiety, and addictions (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). This intervention aims at alleviating pathogenic agents, while also emphasizing on the capacities of mindfulness-based interventions to optimize psychological and behavioral functioning.…”
Section: Introductionmentioning
confidence: 99%